The rise of dual modes of vocational education and training : global emergence, transfer and cross-national attraction - Valiente, Oscar [Herausgeber]; Maitra, Srabani [Herauasgeber]; Gonon, Philipp [Herausgeber]; Pilz, Matthias [Herausgeber] (Routledge, 2026)
"Recognising the regular adoption, by countries across the globe, of the vocational education and training (VET) model already so prevalent in German-speaking countries such as Austria, Germany and Switzerland, this book spotlights dual modes of VET, depicting its global emergence and subsequent cross-national attraction.Globally, the practice of combining schools and workplace practice and learning is seen as a gold-standard for cross-national attraction: the comparison between, and borrowing of, national policies. Using case studies from Eastern Europe, Azerbaijan, India and Latin America, chapters demonstrate how these countries aim to support dual modes of VET to strengthen their own economic and cultural weight abroad, as well as accelerating developmental goals for industry. Further, these countries look to European VET models for integration of their youth both in the labour market and in establishing alternative pathways for young people in the workforce. Chapters discuss the significance of the international context in understanding the nuance involved with duality in VET adoption, as well as shedding light on the transnational diffusion of education policies at both national and global levels. This book will be of use to scholars, postgraduate students and researchers in the fields of international and comparative education, vocational education and training, and adult education and lifelong learning more broadly. Policy makers working in international policy transfer may also benefit from this volume." (Publisher, BIBB-Doku)
E-Book für BIBB-Mitarbeitende über die Bibliothek erhältlich.
Keywords: S System beruflicher Bildung; S 1.3.1 Ausbildung im Dualen System; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; I 2.3.4 Asien; I 2.3.3 Lateinamerika; 370; Berufsausbildung; Duales System; Berufsbildungssystem; Vergleichende Berufsbildungsforschung; Internationaler Vergleich; Transfer; Bundesrepublik Deutschland; Schweiz; Indien; Kosovo; Mexiko; Serbien; Aserbaidschan